PERAN GURU DALAM MENGANTISIPASI PERUNDUNGAN DI LINGKUNGAN SEKOLAH NEGERI 20 KOTA JAMBI - Nasution, Nur Cahaya; Dewantari, Nurul Annisa; Yumarni, Vivi; Zulpianto, Redi (DIRASATUL IBTIDAIYAH, 2024)
AbstrackBullying behavior is currently very common in the school environment. Therefore, schools as a place for students to learn and pursue education have become an environment that is no longer conducive to supporting the learning process. Therefore, this research aims to see the importance of the role of teachers as guides and educators in overcoming bullying behavior that occurs in the classroom. This research is aqualitative descriptive research. The instruments used were observation sheets, interviews and reflections. The conclusion obtained from this research is that teachers as mentors are very important in anticipating and overcoming bullying behavior because teachers act as role models as well as individuals who have authority in the classroom. As a mentor, teacher pay attention to things that can be done, namely giving advice, instilling character education, as well as modeling in the form of active action, namely providing motivation and modeling friendly and polite interaction patterns. The results of the research show that creating a classroom atmosphere that has good communication quality has an impact on reducing bullying behavior in the school and classroom environment. Keywords: Teacher's Role; Anticipating Bullying.